Biological Width around One- and Two-Piece Implants Retrieved from Human Jaws. (23rd June 2014) - Judgar, Ricardo; Giro, Gabriela; Zenobio, Elton; Coelho, Paulo G.; Feres, Magda; Rodrigues, Jose A.; Mangano, Carlo; Iezzi, Giovanna; Piattelli, Adriano; Shibli, Jamil Awad
Abstract : Several histologic studies regarding peri-implant soft tissues and biological width around dental implants have been done in animals. However, these findings in human peri-implant soft tissues are very scarce. Therefore, the aim of this case series was to compare the biological width around unloaded one- and two-piece implants retrieved from human jaws. Eight partially edentulous patients received 2 test implants in the posterior mandible: one-piece (solid implants that comprise implant and abutment in one piece) and two-piece (external hexagon with a healing abutment) implants. After 4 months of healing, the implants and surrounding tissue were removed for histologic analysis. The retrieved implants showed healthy peri-implant bone and exhibited early stages of maturation. Marginal bone loss, gaps, and fibrous tissue were not present around retrieved specimens. The biologic width dimension ranged between 2.55 ± 0.16 and 3.26 ± 0.15 to one- and two-piece implants, respectively (P < 0.05 ). This difference was influenced by the connective tissue attachment, while sulcus depth and epithelial junction presented the same dimension for both groups (P > 0.05 ). Within the limits of this study, it could be shown that two-piece implants resulted in the thickening of the connective tissue attachment, resulting in the increase of the biological width, when compared to one-piece implants.